Profil Sidik Jari Populasi Etnis Manggarai Barat Di Labuan Bajo, Nusa Tenggara Timur, Indonesia - nikmatul iza; Yultiana Januer (IKIP Budi Utomo Malang, 2023)
The aims of this study was to identify the fingerprint patterns of the West Manggarai ethnic in Labuan Bajo, East Nusa Tenggara, Indonesia. This type of research is descriptive-qualitative with a population of 70 original West Manggarai ethnic people. Data collection was carried out by interviewing and filling out information sheets and respondent's approval, then fingerprint patterns were printed. The fingerprint results were agreed by using a fingerprint classification system. The results is the fingerprint patterns in the West Manggarai ethnic group generally have an ulnar loop dominant pattern of 59.14% (414 fingers) and the second dominant pattern plain whorl with a total of 32.71% (229 fingers). The ulnar loop dominant pattern is found on the middle finger (M) and little finger (L), while the second dominant plain whorl pattern is located on the right thumb (T), left index finger (I), and both ring fingers (R).